(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Toothpick is a tool to clean teeth from leftovers tucked in between the teeth. A toothpick that is often used is a stick madefrom wood. We also need to know that objects such as wooden toothpicks can be swallowed by chance and often occur. Agricultural tubers can now be processed into other alternatives for making environmentally friendly toothpicks because wood-based toothpicks can cause natural damage. Some plants that can be processed into toothpicks are sago (Metroxylon sago), ginger (Zingiber officinale), and carrots (Daucus carota). carrot bulbs and ginger tubers. The specific purpose of this research is to find out the most preferred type of plant seeds among sago tubers, carrot bulbs and ginger tubers based on organoleptic assessment (color, aroma, and strength). Method: This type of research used in this study is experimental laboratory research. The research design used was a post test with control group design with samples in this study using 30% sago flour, 30% ginger flour, 30% carrot flour. The organoleptic test used was the hedonic test (preference test) of 15 panelists who were asked to respond to the parameters of color, aroma and breaking strength. Results: The results showed that for the organoleptic assessment of the highest average color treatment found in carrot raw material, 2.73 with a standard deviation of 0.79. For the treatment of aroma, the highest average was found in the ginger raw material, 2.80 with a standard deviation of 0.67. And the highest average fracture treatment was found in ginger which is 2.33 with a standard deviation of 1.04. Conclusion: The results of this study indicate that panelists prefer toothpicks made from ginger tubers rather than toothpicks made from carrot bulbs and sago tubers